Epidemio-Clinical Profile of Psychotrauma in Military Victims of Terrorists Attacks in Benin in December 2021. - AZA-GNANDJI, Guy-Gérard (My University, 2023)
Introduction: In December 2021, Beninese soldiers were victims of armed terrorist attacks. This study aims to determine the psychological impact of the events experienced on the victims in order to better prevent post-traumatic stress disorder. Materials and methods: This is a descriptive cross-sectional study conducted from December 13 to 14, 2021, i.e. 12 days after the oldest event and 4 days after the most recent. The experience of the event was assessed with the Peritraumatic Distress Inventory and the Peritraumatic Dissociation Experiences Questionnaire. Symptoms experienced in the hours and days after the event were assessed with the Revised Event Impact Scale. Results: 36 soldiers were included out of the 38 survivors, i.e. 94.73%. They were 51.43% victims of the night assault, 37.14% of the ambush on patrol and 11.43% of the explosion of vehicle on mine, all male. The average age was 31 years with extremes of 25 and 49 years. The 25 - 30 year olds predominated, 52.78%. 100% of soldiers had significant peritraumatic dissociation, of which 94.44% also had significant peritraumatic distress. 100% of the soldiers had manifestations of intrusion, 89% of manifestations of avoidance and 83% of manifestations of hyperexcitation. 88.89% had an index for acute stress including 100% of victims of night assault and vehicle explosion on mine. Conclusion: This study shows a high prevalence of peritraumatic reactions, recognized factors favoring post-traumatic stress disorder, and the interest of their evaluation for medical and psychological help adapted to the victims
Keywords: Psychotrauma; Peritraumatic Dissociation; Peritraumatic Distress; Terrorist; Attacks; Military